What are the prospects for the hormonal IUD in the public sector? A mixed-method study of the user population in Zambia - Aurélie Brunie; Megan Lydon; Kayla Stankevitz; Namwinga Chintu; Claire Brennan; Kendal Danna; Kate H. Rademacher (BMC, 2022)
Abstract Background The levonorgestrel-releasing intrauterine device (IUD)-also known as the hormonal IUD-is a highly effective contraceptive method that has not been widely available in the public sector in Zambia. Early introduction efforts can provide critical insights into the characteristics of users, reasons for method choice, and experiences getting their method. Methods We conducted a survey with 710 public sector clients who received a hormonal IUD, copper IUD, implant or injectable in two provinces of Zambia, and additional in-depth interviews with 29 women. We performed descriptive analyses of survey data and fitted multivariable logistic regression models to assess factors associated with hormonal IUD use. Qualitative interviews were analyzed thematically. Results Factors associated with hormonal IUD use included full-time or self-employment (relative to both implant and copper IUD use), as well as being older, wealthier, and partner not being aware of method use (relative to implant use only). Common reasons for choosing long-acting methods were duration, perception that the method was "right for my body," and convenience. In addition, a portion of hormonal IUD acceptors mentioned effectiveness, potential for discreet use, few or manageable side effects, and treatment for heavy or painful periods. Between 83 and 95% of women said that they were counseled about menstrual changes and/or non-bleeding side effects; however, more hormonal IUD acceptors recalled being counseled on the possibility of experiencing reduced bleeding (88%) than amenorrhea (43%). Qualitative interviews indicate that women seek methods with minimal or tolerable side effects. While most women reported their partner was aware of method use, men may be more consistently involved in the decision to use contraception rather than in the choice of a particular method. Qualitative results show an appreciation of the lifestyle benefits of reduced bleeding (especially lighter bleeding), although amenorrhea can be cause for concern. Conclusions Initial efforts to introduce the hormonal IUD can provide valuable learnings that can inform broader method introduction to expand choice and better suit women's needs in Zambia and elsewhere. Scale-up plans should include emphasis on high quality counseling and demand generation. Plain English Summary The government of Zambia is committed to increasing access to high-quality contraception and making more choices available to users. To date, the hormonal IUD, a highly effective, long-lasting contraceptive has not been widely available in the country. A study in pilot introduction settings provided insights into why women chose the methods, their characteristics, and their experiences getting their methods. The 710 women in the study received family planning services in public sector settings in two provinces in Zambia. Women in the study who received a hormonal IUD, copper IUD, implant, or injectable completed a quantitative survey; in-depth interviews were also conducted with 29 women. Results showed common reasons for choosing the long-acting methods (hormonal IUD, copper IUD or implants) were their duration, perception that the method was "right for my body," and convenience. In addition, some hormonal IUD acceptors indicated that they were attracted to the method's effectiveness, potential for discreet use, few or manageable side effects, and treatment for heavy or painful periods. Qualitative interviews with women also showed that women want contraceptive methods that lead to minimal or tolerable side effects. Male partners were typically aware of contraceptive use; however, men were less involved with decisions about the particular method women selected. Use of the hormonal IUD can lead to reduced menstrual bleeding, and in the interviews, women indicated that they liked reduced bleeding (especially lighter bleeding), although amenorrhea (paused bleeding) can be cause for concern. The results can help inform broader method introduction.